PENGARUH PARTISIPASI PENYUSUNAN ANGGARAN TERHADAP KINERJA PEJABAT STRUKTURAL DENGAN BUDAYA ORGANISASI DAN KOMITMEN ORGANISASI SEBAGAI VARIABEL MODERASI - Nugroho, Wasono -; -, Sunarso - (Universitas Slamet Riyadi, 2012)
ABSTRACT This study aims to (1) analyze the significance of the effect of participation in budget preparation, organizational culture, and organizational commitment to performance structural officer. (2) analyze the effect of participation in the performance of official budgetary structural moderated by organizational culture (3) analyze the effect of budgetary participation on performance are moderated by officials structural organizational commitment. The population in this study were all middle and lower level leaders are involved in the preparation of the budget in as many as Pemerntahan Grobogan District 294 officials. Total sample as a whole by 74 respondents, taken using the technique of